THE EFFECT OF CONSUMER BEHAVIOR ON CUSTOMERS INTEREST IN MAKING DECISIONS TO BUY FIRE INSURANCE PRODUCTS - Aprilia Nurvita Sari (JURNAL SOCIUS, 2022)
This study aims to determine whether there is an influence between consumer behavior factors on purchasing decisions for fire insurance at PT. Mandiri AXA General Insurance Banjarmasin branch. The type of data used is quantitative research. This data is in the form of data on consumer behavior factors that influence including cultural, social, personal and psychological factors. The population is people - people who have become customers of fire insurance PT. Mandiri AXA General Insurance Banjarmasin branch, totaling 305 people. Sampling in this study using the Slovin formula with a sampling error of 5% so that the number of respondents obtained with a simple random sampling technique